ANALISIS PENGARUH INFRASTRUKTUR EKONOMI DAN UPAH TERHADAP PENANAMAN MODAL ASING DI PULAU SUMATERA - Sonia Pratiwi; Mike Triani (Universitas Negeri Padang, 2019)
This study aims to find out and analyze: (1) The impact road infrastructure on FDI in Sumatera Island. (2) The impact of electricity infrastructure on FDI in Sumatera Island. (3)The impact of telecommunication infrastructure on FDI in Sumatera Island (4) The impact of wage on foreign direct investment in Sumatera Island. (5) The impact of road infrastructure, electricity infrastructure, telecommunication infrastructure and wage on FDI in Sumatera Island. This study used a panel regression analysis with model selected is the Random Effect Model (REM). The results of this study indicate that (1) Road Infrastructure has no impact on FDI in Sumatera Island. (2) Electricity infrastructure has an impact on FDI in Sumatera Island. (3) Telecommunication infrastructure has an impact on foreign investment in Sumatera Island. (4) Wage has no impact on FDI in Sumatera Island, while (5) Together road infrastructure, electricity infrastructure, telecommunication infrastructure and wage has an impact on FDI in Sumatera Island.